Efficiency of secondary education of a selected OIC countries - Mohd Arshad, Mohd Nahar (Mercy College, New York, 2014)
The purpose of this study is to investigate the level of technical efficiency of secondary education in 16 selected OIC countries (including West Bank and Gaza). Education efficiency has become an important issue given the pressing levels of public deficit and debt of many countries. Since the educational sector always receives high priority in budget allocations, an evaluation of whether the allocations made for education has been technically efficient is important. With budget constraints and high expectation by the public to see a continuous improvement in students’ academic achievement, the educational sector has been put under pressure to deliver. The study employs TIMSS 2011 data, involving 40 countries. The technique used to calculate the level of technical efficiency is Data Envelopment Analysis (DEA). Almost all of the 16 selected OIC members are technically inefficient in utilising their educational resources to achieve better TIMSS results in comparison with the non-OIC countries. Even after controlling for the environmental factors, secondary education in the OIC countries remain technically inefficient.